African rhythms the autobiography of Randy Weston - Weston, Randy 1926- (Refiguring American music, 2010)
Arranger's preface -- Origins -- Growing up in Brooklyn -- The scene shifts to the Pacific -- Postwar: escaping the panic -- Post-Berkshires: succumbing to the irresistible lure -- Enter Melba Liston -- Uhuru Afrika : freedom Africa -- Making the pilgrimage -- Touring the motherland -- Making a home in Africa -- Connecting with the Gnawa -- Building a life in Tangier: the African Rhythms Club -- Festival blues, then divine intervention : blue Moses -- Post Morocco and the Ellington connection -- Compositions and sessions -- The African Rhythms Quintet -- The African Queen -- The adventures of Randy Weston -- Ancient future -- Conclusion: Randy Weston-- philosophically yours -- Discography -- Awards and citations